2016
DOI: 10.5606/tftrd.2016.10734
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of spinal curvatures during sitting on a rehabilitation ball versus stool

Abstract: Objectives:This study aims to compare the extent of the spine curvatures in the sagittal plane during corrected sitting on a rehabilitation ball and during sitting on a chair without a backrest. Patients and methods:The study group consisted of 57 subjects (23 males, 34 females; mean age 24.7±2.3 years; range 20 to 32 years). The Moiré method was used to assess the body posture. The tests were conducted using the apparatus for computer assessment of the body posture MORA 4 Generation. The spine curvature was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“… 19 , 31 It was suggested that the spines of patients with decreased curvatures (decreased lordosis or axially extended spines) possess decreased capacity of shock attenuation. 32 …”
Section: Discussionmentioning
confidence: 99%
“… 19 , 31 It was suggested that the spines of patients with decreased curvatures (decreased lordosis or axially extended spines) possess decreased capacity of shock attenuation. 32 …”
Section: Discussionmentioning
confidence: 99%
“…For our research, we used the equipment DIERS based on the principle of the Raster Stereography. One of the reasons why we utilized this tool is that the repeated scanning process does not create undesirable effects for human health [14][15][16].…”
mentioning
confidence: 99%